Japan After Japan : Social and Cultural Life from the Recessionary 1990s to the Present - Harootunian, Harry D., 1929-; Yoda, Tomiko (Book collections on Project MUSE., 2006)
Scholars of history, anthropology, literature, and film explore the transformations in Japanese politics, culture, and society since Japan s recession of the early 1990s.